MODIFICATION OF PLASTIC BALL LEARNING MEDIA TO IMPROVE LEARNING OUTCOMES OF KASTI BALL - Dery Kurniawan; Topo Yono (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2026)
One of the common problems faced by teachers in teaching kasti (traditional baseball) is the limited availability of standard balls, which often hinders students’ participation and learning outcomes. To overcome this problem, this study implemented a modified learning medium by replacing the standard baseball with plastic balls. The purpose of this study was to improve students’ learning outcomes in kasti using modified plastic ball media. This study employed Classroom Action Research (CAR) consisting of two cycles, each comprising planning, implementation, observation, and reflection stages. The participants were 26 tenth-grade students of Bustanul Ulum Vocational High School. Students’ learning outcomes were evaluated based on their performance in kasti skills and learning mastery.The results showed that in Cycle I, 18 students (69%) achieved mastery, while 8 students (31%) had not yet met the learning criteria. After improvements were implemented in Cycle II using plastic ball modifications, all 26 students (100%) achieved mastery. These findings indicate that the modification of plastic ball learning media effectively improved students’ learning outcomes in kasti.